2019
DOI: 10.1186/s12913-019-3940-5
|View full text |Cite
|
Sign up to set email alerts
|

“Struggling with practices” – a qualitative study of factors influencing the implementation of clinical quality registries for cardiac rehabilitation in England and Denmark

Abstract: BackgroundThe use of clinical quality registries as means for data driven improvement in healthcare seem promising. However, their use has been shown to be challenged by a number of aspects, and we suggest some may be related to poor implementation. There is a paucity of literature regarding barriers and facilitators for registry implementation, in particular aspects related to data collection and entry. We aimed to illuminate this by exploring how staff perceive the implementation process related to the regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 35 publications
1
44
0
Order By: Relevance
“…The Consolidated Framework for Implementation Research was used in the interview guide, to ensure that its domains related to effective implementation were covered in the interviews, including intervention characteristics, inner and outer setting, process and characteristics of individuals (Damschroder et al, 2009). The interviews had a two-fold purpose, as they covered the data-entry process (Egholm et al, 2019) and perceptions of feedback. The interview guide was pilot-tested on the target group in Denmark, and a few questions were modified after reflection and comments from the participants After the first interview in the UK, a single question were adjusted to better fit the context of…”
Section: Interview Guidementioning
confidence: 99%
“…The Consolidated Framework for Implementation Research was used in the interview guide, to ensure that its domains related to effective implementation were covered in the interviews, including intervention characteristics, inner and outer setting, process and characteristics of individuals (Damschroder et al, 2009). The interviews had a two-fold purpose, as they covered the data-entry process (Egholm et al, 2019) and perceptions of feedback. The interview guide was pilot-tested on the target group in Denmark, and a few questions were modified after reflection and comments from the participants After the first interview in the UK, a single question were adjusted to better fit the context of…”
Section: Interview Guidementioning
confidence: 99%
“…One of these methods is using coded data and classification systems, especially the use of Orphanet classification, definitions for recording or reporting particular data items due to internationally agreed-upon guidelines (especially in multi-center registries). Other methods also include determining the quality indicators [ 59 , 60 ], such as determining the percentage of missed data [ 61 , 62 ], comparing re-abstracted data with the main data from the data source [ 61 ], auditing the case-finding process, and case reporting [ 63 ] in registry centers over time, data audit with continuous feedback [ 59 , 64 ] by data quality supervisors, data error correction at data entry, automatic data validation [ 64 , 65 ] and warnings about mandatory data elements [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further explanations concerning the use of CQR data can be derived from our previous qualitative studies in the cardiac rehabilitation field. For example, we have found that feedback data may not reach the frontline staff because it fails to pass through complex delivery pathways, staff may not know that local feedback data exists and a culture supporting quality improvement may not have been established31 (Helmark et al ; article accepted for publication). Other plausible explanations, suggested by our previous work and supported by other scholars, are that roles and responsibilities for acting on data are unclear and that there is a general lack of time and understanding regarding the use of CQRs in improvement work in healthcare 15 27 31.…”
Section: Discussionmentioning
confidence: 99%